Evaluating the Performance of Ant Colony Algorithm for the Solution of Constraint Based Traveling Salesman Problem (International Journal of Engineering and Computer Science, 2016)
Soft Computing is the use of inexact solution to computationally hard tasks such as the solution of NP-Complete problems.TSP is a combinatorial optimization problem. In this paper TSP problem has been solved by using ACO. The major drawback of ACO is that it traps in local optima. In order to find an optimal solution for TSP problem the presented paper proposes an improved ACO which produces better result.